Pembelajaran Berdeferensiasi dalam Mata Pelajaran Bahasa Indonesia - Putri Ayu Marshinta Wulandari; Nori Anggraini (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to examine the application of differentiated learning in Indonesian language teaching at the junior high school level through a literature review approach. By analyzing scientific articles relevant to the research title, the author found that differentiated learning is effective in increasing student motivation, engagement, and learning outcomes. In the context of the Merdeka Curriculum, it aligns with the reinforcement of the Pancasila Student Profile and promotes inclusive, student-centered learning. However, its implementation still faces challenges, particularly in terms of teacher readiness and resource limitations. Therefore, ongoing professional development is essential to ensure the successful application of differentiated instruction in Indonesian language classrooms.